2020
DOI: 10.1093/cid/ciaa1055
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in Rural Latin America. A Population-based Study in Coastal Ecuador

Abstract: Antibodies to SARS-CoV-2 were detected in 303/673 rural Ecuadorian adults (45%), 77% of whom had compatible clinical manifestations. Seropositivity was associated with the use of open latrines. Our findings support the fears of mass spread of SARS-CoV-2 in rural Latin America and cannot exclude a contributing role for fecal-oral transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 11 publications
8
63
2
1
Order By: Relevance
“…Given the underlying heterogeneity in IFR that could not be captured by the ensemble model, it is important to consider the full range of uncertainty in these estimates as suggested by individual seroprevalence studies (grey points in Figure 3b). Estimates of high transmission levels in some South American countries are consistent with recent subnational seroprevalence studies [17][18][19] . Our…”
Section: Consistency Of Ifrs Across Serostudiessupporting
confidence: 85%
“…Given the underlying heterogeneity in IFR that could not be captured by the ensemble model, it is important to consider the full range of uncertainty in these estimates as suggested by individual seroprevalence studies (grey points in Figure 3b). Estimates of high transmission levels in some South American countries are consistent with recent subnational seroprevalence studies [17][18][19] . Our…”
Section: Consistency Of Ifrs Across Serostudiessupporting
confidence: 85%
“…Increased seroconversion in individuals using a latrine confirms our baseline seroprevalence findings, consistent with a contributory role of open latrines as a source of infection (fecal contamination) [11]. In addition, we found that a shared latrine was the most likely cause of incident SARS-CoV-2 contagion among several members of two otherwise unrelated families [27].…”
Section: Discussionsupporting
confidence: 86%
“…By May 2020, we conducted a cross-sectional study of SARS-CoV-2 infection in 673/691 (97.4% coverage) of middle-aged and older adults actively enrolled in the Atahualpa Project Cohort. In that study, 303 (45%) participants were positive for SARS-CoV-2 antibodies, 77% of whom were symptomatic [11]. It was also demonstrated a significant association between seropositivity and the use of latrines, suggesting a contributing role for fecal-oral transmission of the disease.…”
Section: Background Datamentioning
confidence: 84%
See 2 more Smart Citations